The State of Europeanisation: between Clash and Convergence. A comparison of the media coverage of the 2019 European Elections in seven countries - Gerret von-Nordheim; Tina Bettels-Schwabbauer; Philip Di-Salvo; Paula Kennedy; Kornélia-R. Kiss; Michal Kuś; Ana Pinto-Martinho; Sandra Stefanikova; Décio Telo (Revista Mediterránea de Comunicación, 2021)
The issue of the Europeanisation of national public spheres is a question as to how a discursive media space can be created within the EU. There are forces of convergence at work, such as networking within the borderless digital space. At the same time, there are counterforces: increasing nationalism and populists who identify ‘Brussels’ as a target for their criticism of elites. The vision of a European public sphere appears to share the same fate as the European project as such; as a result of years of crisis, optimism has given way to disillusion. Using coverage of the 2019 EU elections in seven European countries (a total of 57,943 articles from Germany, Hungary, Italy, Poland, Portugal, the Czech Republic, and the UK), we draw a picture of a heterogeneous EU public. What is particularly clear is that the phenomena of horizontal and vertical Europeanisation require more nuanced interpretations. While a high degree of horizontal Europeanisation indicates convergent and pro-European media coverage (as in the cases of Germany and Portugal), a high degree of vertical Europeanisation may indicate polarised publics or an unfree media landscape (as in the UK and Hungary).